The Influence of Servant Leadership and Organizational Citizenship Behavior on the Performance of Area-Based Empowerment Institutions in East Java - Yuntawati Fristin; Fajar Supanto; Muhammad Firdaus; Ernita Puspasari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines the influence of servant leadership and organizational citizenship behavior on the performance of the Inter-Village Cooperation Agency (BKAD) in East Java through a quantitative approach with a cross-sectional design. Using a sample of 100 BKAD selected by cluster proportional random sampling, the study collected data from multiple informants through structured questionnaires and semi-structured interviews, and analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. The results showed that servant leadership had a significant positive effect on organizational performance (β = 0.366, p < 0.001), with organizational citizenship behavior partially mediating the relationship. Servant leadership was proven to have a positive effect on organizational citizenship behavior (β = 0.293, p = 0.021), which in turn had a positive effect on performance (β = 0.216, p = 0.001). The research findings affirm the importance of servant leadership and organizational citizenship behavior in enhancing the performance of empowerment institutions, which encourages the development of innovative empowerment methods, adaptive training curriculum design, and facilitation of public service-oriented leadership, with recommendations for further research using longitudinal designs and broader geographic coverage.